2014
DOI: 10.1021/es502201s
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Indoor PM2.5 Exposure from Burning Solid Fuels in Vented and Unvented Stoves in a Rural Region of China with a High Incidence of Lung Cancer

Abstract: The combustion of biomass and coal is the dominant source of household air pollution (HAP) in China, and contributes significantly to the total burden of disease in the Chinese population. To characterize HAP exposure related to solid fuel use and ventilation patterns, an exposure assessment study of 163 nonsmoking female heads of households enrolled from 30 villages was conducted in Xuanwei and Fuyuan, two neighboring rural counties with high incidence of lung cancer due to the burning of smoky coal (a bitumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 31 publications
5
116
1
Order By: Relevance
“…Measurements of PM 2.5 and PAH have been described previously (Downward et al, 2014b; Hu et al, 2014) By matching PM 2.5 and PAH measurements to absorbance measurements collected on the same day, we assessed the interrelationship between PM abs and other air pollution components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of PM 2.5 and PAH have been described previously (Downward et al, 2014b; Hu et al, 2014) By matching PM 2.5 and PAH measurements to absorbance measurements collected on the same day, we assessed the interrelationship between PM abs and other air pollution components.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has identified that household air pollution (HAP) related to smoky coal use (when compared to smokeless coal) contains relatively high amounts of particulate matter (PM 2.5 ) and polycyclic aromatic hydrocarbons (PAH) (Downward et al, 2014b; Hu et al, 2014). However, exposure to these compounds alone appears to be insufficient to explain the lung cancer risk in the area, requiring the consideration of alternative pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have examined the health effects of PM 2.5 (Hu et al, 2012;Huang et al, 2012;Yang et al, 2012;Hu et al, 2014), but these previous investigations studied either a single city or a single health impact indicator. In our study, we examined four health endpoints: premature mortality, respiratory diseases, cardiovascular diseases, and chronic bronchitis.…”
Section: The Health Impacts Due To Pm 25mentioning
confidence: 99%
“…Coal combustion related PM 2.5 has been suggested to be toxic for the human health. Combustion of coal was associated with increased mortality, pulmonary inflammation, or lung cancer (Laden et al, 2000;Liberda and Chen, 2013;Hu et al, 2014). Indoor coal combustion related PM 2.5 might have contributed to the adverse effects on lung function found in adult residents in Southwest China (Jie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%